Development of a social distancing monitoring system in Republic of Korea: results of a modified Delphi process - Suin Seo; Jin-Ok Han; Sool Shin; Heeyoung Lee (BMC, 2022)
Abstract Background Social distancing policies work in different ways and at different levels. In addition, various forms of monitoring systems have been implemented in different countries. However, there is an almost complete lack of specific monitoring system in Republic of Korea to effectively monitor social distancing measures compliance and outcome. This study aims to develop a monitoring system for social distancing measures compliance and outcome in Korea to evaluate and improve the implemented policy. Methods A draft monitoring system was developed after reviewing Korea's social distancing measures (central and local government briefings) and checking available data about social distancing behavior. The modified Delphi process was used to evaluate the draft of the social distancing monitoring system. In total, 27 experts participated in the evaluation. The round 1 evaluation includes (1) commenting on the composition of the monitoring fields (open response), (2) monitoring indicators for each monitoring field (10-point Likert scale), and (3) commenting on the source of data used to develop the monitoring system (open response). In the round 2 evaluation, 55 indicators, excepting open responses, were re-evaluated. Results The response rate for the Delphi survey was 100% in both the first and second rounds. Of the 55 indicators, 1 indicator, which did not satisfy the quantitative criteria, was excluded. According to the experts' open response comments, 15 indicators were excluded, as these indicators overlapped with other indicators or had little relevance to social distancing. Instead, 23 new indicators were added. Finally, 62 indicators were included with 12 available data sources. The monitoring system domain was divided into 'social distancing measures state, social distancing measures compliance, social distancing outcome'. Conclusions This study is significant in that it is the first in Korea to develop a comprehensive monitoring system for checking if social distancing measures are being followed well, and is applicable to estimates utilizing data that are immediately available for each indicator. Furthermore, the developed monitoring system could be a reference for other countries that require the development of such systems to monitor social distancing.